Modelling of heat transfer process in condensing unit with titanium alloy tubes; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Lavrinenko S. V. Sergey Viktorovich; Polikarpov P. Pavel; Matveeva A. A. Anastasiya Aleksandrovna; Martyshev V. N. Vladimir Nikolaevich (2017, 2017)
Title screen